2023
DOI: 10.1021/jacs.3c03897
|View full text |Cite
|
Sign up to set email alerts
|

Postsynthetic Annulation of Three-Dimensional Covalent Organic Frameworks for Boosting CO2 Photoreduction

Abstract: Three-dimensional covalent organic frameworks (3D COFs), with interconnected pores and exposed functional groups, provide new opportunities for the design of advanced functional materials through postsynthetic modification. Herein, we demonstrate the successful postsynthetic annulation of 3D COFs to construct efficient CO2 reduction photocatalysts. Two 3D COFs, NJU-318 and NJU-319Fe, were initially constructed by connecting hexaphenyl-triphenylene units with pyrene- or Fe-porphyrin-based linkers. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…Photocatalysis: (a) heteroatom COFs with dithiol units for photocatalytic CO 2 RR; (b) 3,3′,5,5′-tetraformyl-4,4′-biphenyldiol-COF with a salicylideneaniline (SA) ligand (TFBD-COF-Co-SA) with Co–N 2 O 2 sites for photocatalytic CO 2 RR; (c) metal-salen-based COF with pyrene light-harvesting units for photocatalytic HER; (d) porphyrinic pyrazine-based COF with hydrophilic group interfacial design for photocatalytic HER; (e) 3D COF via postsynthesis for photocatalytic CO 2 RR. Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Cof-based Sacsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photocatalysis: (a) heteroatom COFs with dithiol units for photocatalytic CO 2 RR; (b) 3,3′,5,5′-tetraformyl-4,4′-biphenyldiol-COF with a salicylideneaniline (SA) ligand (TFBD-COF-Co-SA) with Co–N 2 O 2 sites for photocatalytic CO 2 RR; (c) metal-salen-based COF with pyrene light-harvesting units for photocatalytic HER; (d) porphyrinic pyrazine-based COF with hydrophilic group interfacial design for photocatalytic HER; (e) 3D COF via postsynthesis for photocatalytic CO 2 RR. Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Cof-based Sacsmentioning
confidence: 99%
“…Synthesizing COFs in 3D geometry could also be a solution to promoting the catalytic reactivity in CO 2 reduction (Figure e). Recently, Lei and co-workers synthesized NJU-318 and NJU-319Fe 3D COFs via the condensation of 6-connected 2,3,6,7,10,11-hexakis(4-formylphenyl)triphenylene (HEPTP) with 1,3,6,8-tetrakis(4-aminophenyl)pyrene (PyTTA) and tetrakis(4-aminophenyl)porphyrin (TAPP) as linkers, respectively (Figure a) . Then they postmodified the COFs to extended π-conjugated networks by transforming the hexaphenyltriphenylene moiety to hexabenzotrinaphthylene (Figure b), which cannot be synthesized directly due to the low solubility of the extended π-conjugated linker.…”
Section: Cof-based Sacs For Photocatalytic Energy Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent organic frameworks (COFs) have gained significant attention due to their stable covalent bonds and remarkable properties, such as high chemical stability, large specific surface area, excellent biocompatibility, and customizable constituent units. These unique characteristics endow COFs with high versatility for various applications, including gas storage, , catalysis, , environmental remediation, ,, bioimaging, , drug delivery, , and biosensing. , Recently, significant efforts have been devoted to preparing uniform COF nanoparticles (COF NPs), and the improved tunability and bioavailability can boost the biomedical applications of COFs. , Moreover, efforts are made to make full use of the advantages of COFs in their modifiability with different functional groups, , which allows the postsynthetic modification to achieve tailored properties, including proton conductivity, , photocatalytic activity, , and fluorescence characteristic. , For instance, recent research studies have shown that postmetallized COFs can be used for electrocatalysis, , water decomposition, , and CO 2 reduction. , In these reports, metal ions were strategically modified on COFs, which could remarkably improve the performance of the materials and play important roles in enzymatic catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are a class of crystalline porous material and feature many advantages, including good chemical and thermal stability, high porosity, and adjustable structure, and thus render them an ideal choice in various applications, such as heterogeneous catalysis, energy storage, drug delivery, photoelectric devices, and gas separation and storage. To date, versatile two-dimensional (2D) and three-dimensional (3D) COFs with different topologies, such as kgd , hcb , sql , hxl , pcb , flu , and kg m , are constructed and investigated for the applications in above-mentioned fields. The kg m topology is a typical 2D COF structure that has a characteristic double-pore configuration consisting of triangular micropores and hexagonal mesopores.…”
mentioning
confidence: 99%